PEMENUHAN HAK PENYANDANG DISABILITAS BIDANG KETENAGAKERJAAN DI KOTA SEMARANG (IMPLEMENTASI PERDA JAWA TENGAH NO. 11 TAHUN 2014 TENTANG PEMENUHAN HAK PENYANDANG DISABILITAS) - Dessy Grestika Ratna; Kismartini Kismartini (Journal of Public Policy and Management Review, 2018)
The purpose of this research is to analyze the implementation of the Policy on the Fulfillment of the Rights of Persons with Disabilities in the field of employment in Semarang City, as well as the supporting and inhibiting factors of implementing the Policy on the Fulfillment of the Rights of Persons with Disabilities. The method used in this research is descriptive qualitative method, data source used is primary data source and secondary data. The results showed that the fulfillment of Disability Rights in the field of employment in the city of Semarang has not been optimally viewed from 3 aspects of implementation, what happen, and implementation achievement. Viewed from the aspect of the implementation is good because the implementation is done by all agencies with their respective jobs aspects of what happen is not good because the law is still referring to the old law and the city of Semarang still do not have a local law. The aspect of achievement of the implementation has not been achieved as stated in the Regional Regulation of Central Java no. 11 Year 2014 on the Fulfillment of the Rights of Persons with Disabilities. Causes of not yet optimal implementation of this policy is the absence of funds from the APBD, there is no special staff in Dinasker for people with disability and social environment factors -culture and technology in the city of Semarang. The author’s suggestion is allocating funds from APBD, establishing special staff for the implementation of the fulfillment of the rights of people with disability, making SOP for the policy of the fulfillment of the rights of people with disability and make sosialization to change the mindset of the community should not be ashamed of the existence of PwDs and also the mindset of PwDs in order not to always feel pity.